Edukasi Gizi mengenai ASI Eksklusif pada Ibu Hamil dan Menyusui di Bogor Tengah - Fayasari, Adhila; Saputri, Ananda Egy; Allifiya, Bella Nur; Diani, Dita; Afraihana, Nur (Universitas Baiturrahim, 2024)
One of the factors that influences the nutritional status of infants is optimal intake, especially at <6 months of age. Exclusive breastfeeding provides many benefits for infants and mothers. However, exclusive breastfeeding coverage in the Central Bogor area is still low, so it is necessary to understand the perceptions regarding exclusive breastfeeding among mothers, companions, and cadres more deeply.This activity aims to increase mothers' knowledge of providing exclusive breastfeeding for their toddlers from 0-6 months. Community Service (PkM) was carried out in the Cibogor area, Central Bogor for pregnant women, breastfeeding mothers, breastfeeding companions, and cadres in December 2022, including educational outreach using flip sheets, leaflets, and teaching aids, interspersed with games, as well as evaluation using pre-post tests.The number of participants was 17 people consisting of pregnant women, breastfeeding mothers, and companions consisting of family and cadres. PkM ran smoothly, participant interest was very good, and participants actively discussed. This activity shows that there is an increase in knowledge of mothers, companions, and cadres regarding the importance of providing exclusive breastfeeding and good food for breastfeeding mothers by 73%.This PkM activity was successful in increasing knowledge regarding exclusive breastfeeding, especially for pregnant and breastfeeding mothers.Conducting educational activities alongside ongoing support for pregnant and breastfeeding mothers would be most effective if implemented on a regular basis